(3QSGdI aj JYdje GdeYGdLGJs - (3GHbQGW GdMcjes
(3ChdgG (B:s
(3QSGdI dHbQGW GdMcje ai JYdje GdeYGdLGJ hJQZjH GdfGS HGSJYeGd GdWH ai GdCMhGd s
(3BNQgG (B:s
(3hGdOhGe Ydjg HfbU GdOeGZ jhQK GdUOGY hjPgH HGdYbd hGdHUQ hjaSO GdHOf Je HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs